Kinerja Belanja Pemerintah Daerah Kota Kediri Tahun 2018-2023 - Wulandari, Catur; Sofa, Indah Ainus; Ardiansyah, Moh; Aisyah, Sindy Nur; Sasongko, Wahyu Isnu; Hapsari, Mega Tunjung (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
The purpose of this research is to analyze the financial performance of the Kediri City government in 2018-2023. This research uses a quantitative approach with descriptive analysis methods. The data comes from Kediri City regional expenditure data for the 2018-2023 period, which was obtained through the Kediri City Central Statistics Agency and the Kediri City Regional Revenue, Financial and Asset Management Agency. The data is processed using regional financial ratio analysis. This research shows that the average expenditure growth ratio of the Regional Government of Kediri City is not good because expenditure growth exceeds income, the average capital expenditure is 10.91% indicating good performance in regional development, the average percentage of operating expenditure is 85, This 45% shows that the operational expenditure performance of the City of Kediri during the 2018-2023 period showed good performance.